Immunotherapies Targeting Fish Mucosal Immunity – Current Knowledge and Future Perspectives - Koshio, Shunsuke (Frontiers in Immunology, 2016)
In recent years, studies on the mucosal immunity in fish species have shown much progress. Although there are some organs such as skin, gills, and gut are directly associated with the mucosal immunity of fish species, this mini review emphasizes the general knowledge on the role and production figures of skin mucus and factors affecting the secretion of skin mucus of fish species. As the skin mucus of fish species is the first defense line for protection against invading microorganisms such as pathogens (bacteria, virus), parasites, etc., the information for understanding the roles of the skin mucus is very important. Furthermore, the information in the review will shed light on the development of high quality aquafeeds for the sustainable aquaculture field as well.